Identification of damage and fracture modes in power electronic packaging from experimental micro-shear tests and finite element modeling. (1st February 2018) - Msolli, S.; Baazaoui, A.; Alexis, J.; Kim, H.S.
Highlights: Experimental characterization of candidate junctions for power electronic applications. Fracture mechanism of each junction is identified using shear test. A mixed fracture can produce either in the interface or in the junction itself (cohesive). Finite element modeling of the crack initiation and propagation in the junction. Numerical simulations using GTN and CZM models reproduce experimental observations. Abstract: Micro-shear tests are performed in order to characterize the mechanical behavior and the fracture of the chip/metallized ceramic substrate assemblies of power electronic devices. These assemblies are elaborated using three types of junctions: AuGe solder/ Au or Ag finish, transient liquid phase bonding (TLPB) AgIn / Ag finish and Ag nanoparticles/ Au or Ag finish. The experiments are associated to finite element simulations of both nano-indentation and micro-shear tests. The mechanical behavior of the different assembly interfaces is represented using an in-built cohesive zone model (CZM) available in the user friendly finite element code Abaqus®. It is worth noting that the fracture mechanisms observed during the test and service periods of the power electronic packaging are not only due to the debonding at the interfaces but also to the initiation and growth of voids in the joint. Therefore, in addition to the CZM model, Gurson-Tvergaard-Needlmann (GTN) damage model is used in combination with the Rice bifurcation theory to correctly describe the fracture in the joint and, therefore the overall fracture mechanism of the entire junction. The simulation results are compared with the experimental force displacement curves and the SEM observations in order to assess the implemented model.